(untitled) (American Journal of Islam and Society, 2009)
In the introduction and the first section, the authors provide an overview of their book and approach. According to them, every social worker needs to be familiar with the aforementioned concepts when dealing with Muslim clients. Throughout the book, the authors define the pillars and values of Islam and shed light on the real meaning of some of the words that became highly mediatized after 9/11, such as jihad, niqab, honor, women’s rights, marital violence, and homosexuality ...